(untitled) (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
In this paper, I am reviewing autoethnographic method in translanguaging research. I tell a story that is based on a casual and unplanned encounter with Omphile, a seven year old boy with whom I interacted using communicative practices that confirmed the suppositions of translanguaging theory but also challenged the methods that support empirical observations of translanguaging research–in equal measure. The paper signposts the promises that autoethnographic approaches hold for researching naturalistic human communication in ways that side step the language and methods of the positivist tradition. I argue that in the same way that contemporary sociolinguistics theorisations remind us about how communication is not limited to determinate languages or codes, research does not have to be limited to controlled, systematic scientific methods. The framework of autoethnography reviewed in this article is one example of a praxis that is antimethodological and, thus in line with many of the anti-foundational premises of translanguaging theory.